Improved Efficiency of Polymer Solar Cells by means of Coating Hole Transporting Layer as Double Layer Deposition - T Chonsut; N Kayunkid; S Rahong; A Rangkasikorn; S Wirunchit; A Kaewprajak; P Kumnorkaew; J Nukeaw (My University, 2017)
Polymer solar cells is one of the promising technologies that gain tremendous attentions in the field of renewable energy. Optimization of thickness for each layer is an important factor determining the efficiency of the solar cells. In this work, the optimum thickness of Poly(3,4-ethylenedioxythione): poly(styrenesulfonate) (PEDOT:PSS), a famous polymer widely used as hole transporting layer in polymer solar cells, is determined through the analyzing of device's photovoltaic parameters, e.g. short circuit current density (Jsc), open circuit voltage (Voc), fill factor (FF) as well as power conversion efficiency (PCE). The solar cells were prepared with multilayer of ITO/PEDOT:PSS/PCDTBT:PC70BM/TiOx/Al by rapid convective deposition. In such preparation technique, the thickness of the thin film is controlled by the deposition speed. The faster deposition speed is used, the thicker film is obtained. Furthermore, double layer deposition of PEDOT:PSS was introduced as an approach to improve solar cell efficiency. The results obviously reveal that, with the increase of PEDOT:PSS thickness, the increments of Jsc and FF play the important role to improve PCE from 3.21% to 4.03%. Interestingly, using double layer deposition of PEDOT:PSS shows the ability to enhance the performance of the solar cells to 6.12% under simulated AM 1.5G illumination of 100 mW/cm2.
Keywords: Deposition; Open-circuit voltage; Active layer; Organic Electronics and Photovoltaics